92.0k views
4 votes
1/3y + 8/3y = 9/3y for y not = / / / (fraction over fraction over fraction) simplify the sum. State any restrictions on the variable

1 Answer

6 votes

Answer:


(1)/(3)y+(8)/(3)y=(9)/(3)y

Explanation:

As the given expression


(1)/(3)y+(8)/(3)y=(9)/(3)y

Simplifying the left side of the expression


(1)/(3)y+(8)/(3)y


\mathrm{Factor\:out\:common\:term\:}y


=y\left((1)/(3)+(8)/(3)\right).....A

Solving


(1)/(3)+(8)/(3)


\mathrm{Apply\:rule}\:(a)/(c)\pm (b)/(c)=(a\pm \:b)/(c)


=(1+8)/(3)


\mathrm{Add\:the\:numbers:}\:1+8=9


=(9)/(3)

so the equation A becomes


=(9)/(3)y

Therefore,


(1)/(3)y+(8)/(3)y=(9)/(3)y

User ITisha
by
5.5k points